PENERAPAN GEOCENTRIC STAFFING DALAM PEREKRUTAN KARYAWAN TINGKAT MANAJERIAL IBU KOTA NUSANTARA (IKN) DI BIDANG TRANSFORMASI HIJAU DAN DIGITAL - Paretta, Shelomita; Sadihatmanta, Benedicta Gisella; Samantha, Maria; Jaya, Vionna; Sihotang, Rahel Noprianti; Hartadi, Haris; Jonathan, Jonathan; Alexandra, Jessica (PT. Banjarese Pacific Indonesia, 2023)
This research aims to explore and evaluate the implementation of the geocentric staffing approach in the managerial employee recruitment process at the Capital of Nusantara (IKN). The geocentric approach considers qualifications, skills, and experience without regard to the candidate's country of origin. The research methodology involves a case study and analysis of managerial recruitment data. Through a qualitative approach, this study evaluates the effectiveness of geocentric staffing in creating a diverse managerial team and supporting the development goals of IKN. However, implementation challenges such as cultural differences, communication, and individual expectations are also highlighted in this research. By understanding these challenges, the study offers strategic recommendations to enhance the effectiveness of Geocentric Staffing implementation in IKN.